2018
DOI: 10.1016/j.neuron.2018.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Brain Somatic Mutations in MTOR Disrupt Neuronal Ciliogenesis, Leading to Focal Cortical Dyslamination

Abstract: Focal malformations of cortical development (FMCDs), including focal cortical dysplasia (FCD) and hemimegalencephaly (HME), are major etiologies of pediatric intractable epilepsies exhibiting cortical dyslamination. Brain somatic mutations in MTOR have recently been identified as a major genetic cause of FMCDs. However, the molecular mechanism by which these mutations lead to cortical dyslamination remains poorly understood. Here, using patient tissue, genome-edited cells, and mouse models with brain somatic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 71 publications
6
106
1
Order By: Relevance
“…All these changes, together with the enrichment of the mTORC2 downstream signalling pathway, suggest that abnormal expression of PARK7 and GAP-43 might be a result of the dysregulation of the mTOR pathway in the PPS model. Indeed, the mTOR pathway has been shown to be involved in many neurological disorders, such as autism spectrum disorders 47,48 , Alzheimer's disease, tuberous sclerosis complex 46,49,50 , focal cortical dysplasia 51,52 and, more recently, intractable epilepsy 49,[53][54][55][56][57][58] . The mTORC1 and mTORC2 complexes are also upregulated in tissue from patients with MTLE 59 .…”
Section: Discussionmentioning
confidence: 99%
“…All these changes, together with the enrichment of the mTORC2 downstream signalling pathway, suggest that abnormal expression of PARK7 and GAP-43 might be a result of the dysregulation of the mTOR pathway in the PPS model. Indeed, the mTOR pathway has been shown to be involved in many neurological disorders, such as autism spectrum disorders 47,48 , Alzheimer's disease, tuberous sclerosis complex 46,49,50 , focal cortical dysplasia 51,52 and, more recently, intractable epilepsy 49,[53][54][55][56][57][58] . The mTORC1 and mTORC2 complexes are also upregulated in tissue from patients with MTLE 59 .…”
Section: Discussionmentioning
confidence: 99%
“…The specific morphology and dynamic behavior of oRG cells contribute to the proliferative expansion of the cortex and provide a scaffold upon which neuronal migration of the cortex depends. pathway in mouse models have identified phenotypic changes to neuronal size, morphology, and laminar position that resemble disease features of cortical malformations (Hu et al, 2018;Nguyen et al, 2019;Park et al, 2018). However, questions remain regarding the effects of mTOR dysregulation on progenitor cells as well as relevant differences between human and mouse cortical development.…”
Section: Introductionmentioning
confidence: 99%
“…A direct link between autophagy and epileptogenesis was first supported by studies showing that rapamycin, an inhibitor of the mTOR pathway and a powerful autophagy inducer, strongly modulates seizures in several models (Giorgi et al, 2015). Germline and somatic mutations in genes of the mTOR pathway have been identified in patients with various epileptic disorders (Parrini et al, 2016), and a direct contribution of defective autophagy has been confirmed (Yasin et al, 2013;Park et al, 2018). Hypofunctional mutations in TSC1 or TSC2 in tuberous sclerosis result in the uncontrolled activation of the mTORC1 pathway (Lipton and Sahin, 2014) and subsequent inhibition of autophagy directly linked to epileptogenesis in a forebrain-specific conditional TSC1 mouse model (McMahon et al, 2012).…”
Section: Autophagy and Neurodevelopmental Disorder With Epilepsymentioning
confidence: 99%
“…The autophagy impairment due to somatic-activating mutations in MTOR leads to abnormal accumulation of the OFD1 protein at centriolar satellites and disruption of neuronal ciliogenesis. Impaired ciliogenesis abrogates Wnt signaling, which is required for neuronal polarization, and underlies cortical dyslamination reported in patients (Park et al, 2018).…”
Section: Autophagy and Neuronal Polaritymentioning
confidence: 99%